Solutions for business, culture and religion in Eastern Europe and beyond : the 2016 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC) /: the 2016 Griffiths School of Management Annual Conference on Business, Entrepreneurship and Ethics (GSMAC). ([2018]) - Unknown
No abstract available